Price Distortions and Resource-Use Efficiency in Indian Agriculture: A Restricted Profit Function Approach - Kumbhakar, Subal C.; Bhattacharyya, Arunava (The Review of Economics and Statistics, 1992)
Subal C. Kumbhakar, Arunava Bhattacharyya, Price Distortions and Resource-Use Efficiency in Indian Agriculture: A Restricted Profit Function Approach, The Review of Economics and Statistics, Vol. 74, No. 2 (May, 1992), pp. 231-239